An Israelite Village from the Days of the Judges - Kokhavi, Mosheh (The Biblical archaeology review, 1978)
One of the most critical battles in early Israelite history was fought about 1050 B.C. between the Israelites and the Philistines. At that time, the Bible tells us, the twelve tribes had settled the land and the Ark of the Covenant had been installed at Shiloh under the authority of Eli the High Priest. […]